Association of Class Attendance and Test with Grades Attained in BDS Final Professional - Aqib Sohail; Shakila Zaman; Nafees ud Din; Irfan Shah; Aneela Amjad (Gandhara University, 2021)
OBJECTIVES: The purpose of this study was to verify the association of class attendance percentage, and regular test marks of each taught subject in BDS final year with marks obtained in final examination. METHODOLOGY: Class attendance and test performance records of all participants were obtained from the college authority, and the final professional examination marks sheet issued by UHS was obtained from the college office. Potential confounders like age, gender and parents' occupation were also recorded for each student. Pearson's correlation coefficient test was applied to verify the association of class attendance and class tests marks percentage for different subjects taught with final marks. Multivariate analysis was undertaken by adjusting for confounders in the model. RESULTS: This study found significant correlation between each taught subject class test marks with final marks obtained in each respective subject of the final year. Class attendance of each taught subject had weak, insignificant association with final marks except in one subject i.e., Operative Dentistry. CONCLUSION: Class test marks are a stronger predictor of final examination marks than class attendance percentage.